Bilateral anterior congenital radial head dislocation in adults: a case report and literature review - Gao, Jiahao; Tang, Jinshuo; Li, Menglong; Li, Haitao; Peng, Yachen; Wang, Chenyu; Liu, Tong; Zuo, Jianlin (Frontiers in Surgery, 2023)
Objective: Congenital dislocation of the radial head (CRHD) is a rare condition, with bilateral anterior cases being even less common worldwide. Only a few cases had residual pain after adulthood, even when left untreated. Herein, we describe an adult case of bilateral anterior CRHD with significant pain and snapping during motion. The aim of this study was to report the physical and radiological findings, treatment methods, and short-term outcomes of our case, meanwhile, to review adult CRHD cases in the literature. Patient: A 21-year-old male patient presented to our hospital with chief complaints of snapping and exacerbated pain during motion in his left elbow. Diagnoses and Interventions: Detailed medical history and physical examination (PE) results were recorded. Radiographic examinations were performed on the bilateral elbow, and the diagnosis of bilateral anterior congenital radial head dislocation was confirmed. To relieve the pain and snapping in the left elbow, we performed open reduction and fixation of the radial head with annular ligament reconstruction and ulnar osteotomy. Postoperatively, the elbow rested at 90° flexion with a cast for 16 weeks, and the K-wire was removed on the 10th week; afterwards, active functional exercises were performed. Outcomes: The patient was followed-up for 1 year. The pain in his left elbow was relieved with a reduction in the visual analog scale (VAS) score from 7 to 3. The range of motion (ROM) of the left elbow was changed from 0°-135°(preoperative) to -5°-120°(postoperative) (extension-flexion) without any snapping. However, restrictions in external rotation have not yet been fully resolved. Further physical rehabilitation is required. Conclusion: When managing patients with congenital radial head dislocation, the contralateral elbow should be evaluated to identify potential bilateral cases. Surgical options should be discussed with adult patients only for the strong need for functional improvement, although the outcomes may not be fully satisfactory.